A Comprehensive E-prescribing Model to Allow Representing, Comparing, and Analyzing Available Systems - Marceglia, S.; Mazzola, L.; Bonacina, S.; Tarquini, P.; Donzelli, P.; Pinciroli, F. (Methods of Information in Medicine, 2013)
Background: Even though ePrescribing systems are now available in many healthcare systems and have been a crucial milestone of the roadmaps towards eHealth in the last years, there is still a large heterogeneity among functionalities and performances of different systems.Objective: In this paper, we propose an updated comprehensive model for the ePre-scribing process able to represent, analyze, and compare current systems and to support the design of new, more general, systems suitable also to sustain the ePrescription process in National Healthcare Systems.Methods: After a preliminary literature review, we identified six main phases of the ePrescribing process, namely Assign, Transmit, Dispense, Administer, Monitor, and Analysis & Decision. Each phase produces a digital object characterized by formal properties that ensure the collection of appropriate data and information and works as input for the next one. The impact, in terms of benefits, of ePrescribing on governance, drug sur -veillance, and quality of care at the individual, territorial, and governmental levels are related to the formal properties of the digital objects created at the end of each phase.Results and Conclusions: The model-based implementation of each phase has an impact on the quality of care, the access to care, and the effectiveness of care delivery. The model does not cover cost evaluation, but the benefits identified can be used as basis for cost-benefit or cost-effectiveness analysis of heterogeneous systems.
Keywords: ePrescribing process; modelling; national healthcare system; healthcare information system; quality of care